Effects of laser temporal profile on fast electron characteristics - Hata M. (EPJ Web of Conferences, 2013)
2D PIC simulations for fast ignition with a planar target and an ultrahigh intensity laser have been performed to investigate effects of laser temporal profile on fast electron characteristics. Six different laser profiles, which are combination of two pulse shapes, namely Flattop and Gaussian shapes, and three different maximum intensities 1 × 1020, 5 × 1019, and 2.5 × 1019  W/cm2, are studied under the condition of fixed laser energy. Time-integrated energy spectra, coupling efficiencies from the heating laser to fast electrons, and divergence angle of fast electrons are shown and discussed.